INTENSITAS PERCERAIAN DI PENGADILAN AGAMA KABUPATEN PASURUAN TAHUN 2022-2023 - Imanuddin Abil Fida; Haidir Sabaruddin (USRAH: Jurnal Hukum Keluarga Islam, 2024)
Marital relationships are the most important thing in fulfilling human biological needs. However, domestic life after marriage is not as easy as imagined In Indonesia, divorce cases are still widespread. Especially in Pasuruan Regency in 2022 the intensity of cases found was 2,428 and in 2023 at the beginning of January there were 299 divorce cases. Most of these divorce cases are lawsuit divorces. The reason given by the plaintiff was the economic crisis. This context serves as the basis for the study conducted. The aim is to determine the intensity of divorce in Pasuruan Regency. The research uses the library research method. The data obtained by researchers uses a quantitative approach, namely quantitative data collecting divorce data at the Pasuruan Regency Religious Court (PA) through online media, namely through news reports from the Pasuruan Regency Religious Court. Keywords: Intensity; Divorce; Religious Courts.